Bound state solutions of the Schrodinger equation for the modified Kratzer potential plus screened Coulomb potential - Edet, C. O.; Okorie, U. S.; Ngiangia, A. T.; Ikot, A. N. (Indian journal of physics, 2020)
We obtained an approximate solution of the Schrodinger equation for the modified Kratzer potential plus screened Coulomb potential model, within the framework of Nikiforov–Uvarov method. The bound state energy eigenvalues for N 2 , CO, NO, and CH diatomic molecules were computed for various vibrational and rotational quantum numbers. Special cases were considered when the potential parameters were altered, resulting into modified Kratzer potential, screened Coulomb potential, and standard Coulomb potential, respectively. Their energy eigenvalues expressions and numerical computations agreed with the already existing literatures.